Corporate Social Responsibility and the Social Enterprise - Cornelius, Nelarine (Journal of business ethics, 2008)
In this article, we contend that due to their size and emphasis upon addressing external social concerns, the corporate relationship between social enterprises, social awareness and action is more complex than whether or not these organisations engage in corporate social responsibility (CSR). This includes organisations that place less emphasis on CSR as well as other organisations that may be very proficient in CSR initiatives, but are less successful in recording practices. In this context, we identify a number of internal CSR markers that may be applied to measuring the extent to which internal CSR practices are being observed. These considerations may be contrasted with the evidence that community based CSR activities is often well developed in private sector small to medium sized enterprises (SMEs) (Observatory of European SMEs, 2002), a situation which may be replicated in social enterprises especially those that have grown from micro-enterprises embedded in local communities. We place particular emphasis upon the implications for employee management. Underpinning our position is the Aristotelian-informed capabilities approach, a theory of human development and quality of life, developed by Sen (1992; 1999) and Nussbaum (1999) which has been developed further, in an organisational context, (e.g., Cornelius, 2002); Cornelius and Gagnon, 2004; Gagnon and Cornelius, 1999; Vogt, 2005. We contend that the capabilities approach offers additional insights into CSR in social enterprises in general and internal CSR activity in particular. Our article concludes with proposals for future research initiatives and reflections upon social enterprise development from a capabilities perspective.